Intellectual Property Law in Bankruptcy Resolution - Nainggolan, Bernard (Universitas Islam Sultan Agung, 2021)
This research analysis the important role of Intellectual Property Rights (IPR) in the context of bankruptcy law and Postponement of Debt Payment Obligations (Penundaan Kewajiban Pembayaran Utang/PKPU) in Indonesia. Articles in the Civil Code, such as Article 1233, as well as bankruptcy regulations regulate obligations and protection regarding company debt. Curators and company administrators play an important role in managing bankrupt company assets, including IPR. However, optimal management of IPR is often overlooked in bankruptcy resolution efforts, which should take into consideration the peace and continuity of the company's business. This research uses sociological or socio-legal methods. This method is a type of research that focuses on empirical-quantitative observation and analysis which focuses on collecting and examining secondary data, which is then followed by direct research on primary data obtained from the field or community. This research emphasizes the need for optimal recognition and management of IPR in the bankruptcy process to maximize the value of company assets and support financial recovery.